The mediating role of team performance between affiliative leadership and project success in the IT Sector - Wahab, Aqeel; Shaukat, Muhammad Bilal; Nasir, Moeen ud Din (JISR management and social sciences & economics, 2023)
By utilizing the Resource Based View theory, this research seek to establish the effect of affiliative leadership on project success. This study further examines the mediating role of team performance in the given relationship. The data was gathered from a sample of 300 project-team professionals employed within the IT sector of Pakistan. The PLS-SEM method was used to test the direct and mediating impacts. The findings indicated a significant influence of a affiliative leader on project success, with team performance playing a mediating role. The result showed that affiliative leader significantly influences project success and the team performance mediates the relationship between affiliative leadership and project success. This research stands out as one of the few studies that delve into the inter-relationships between affiliative leadership, project success, and team outcomes. It is worth noting that research in the developing countries context is notably scarce in this area. This study makes a significant contribution in IT sector by validating that affiliative leadership impacts project success while team performance mediates this relation. Our research brings a dual contribution to the literature, emphasizing the originality of our study. It establishes connections between affiliative leadership, team performance, and project success within the framework of the Resource-Based View, focusing on the unique context of the thriving IT sector in Pakistan. This originality extends our findings’ applicability to practitioners and researchers in diverse settings.